Analisis Pembelajaran Siswa Kelas III dalam Membaca Intensif Teks Naratif di Sekolah Dasar - Nabilla Muchmaina; Chandra Chandra; Salmaini Safitri Syam (Semantik : Jurnal Riset Ilmu Pendidikan, Bahasa dan Budaya, 2025)
This research focuses on examining the intensive reading learning process of third-grade elementary students when engaging with narrative texts. The objective is to investigate students' ability to comprehend the narrative structure, interpret meanings, and respond to the messages within the text. Employing a qualitative descriptive method, the data were obtained through direct classroom observation, interviews with teaching staff, and evaluation of students’ reading tasks. The findings reveal that although students demonstrate interest in reading narratives, many still struggle to recognize essential components such as plot sequences, character development, and moral lessons. Teachers are instrumental in facilitating students' understanding by implementing supportive strategies, including guided reading, interactive questioning, and the integration of visual materials. The study highlights the importance of a well-structured and supportive learning environment to foster students’ reading comprehension and critical engagement with texts.